A history of ancient Greece - Orrieux, Claude, 1928-1994. (Malden, Massachusetts)
xv, 432 sayfa
Keywords: “This is a major, single-volume introduction to the whole of Ancient Greek History. It covers the period from the Golden Age of Knossos and Mycenae to the incorporation of Greece into the Roman Empire in the second century BC and the transfer of Greek culture to Byzantium in the fourth century AD. The book combines narrative and socio-economic history to cover all regions of Greece, including territories on the edge of the Greek and Hellenistic worlds, as well as the traditional centres such as Athens and Sparta.” --